DEVELOPMENT OF THE MANAGEMENT SYSTEM OF AN EDUCATIONAL INSTITUTION IN THE CONTEXT OF FORMING A POSITIVE IMAGE - VORONKO-NEVIDNYCHA, Tetiana; ISHCHEIKIN, Tymur; SOBCHYSHYN, Vitaliy; RADIONOVA, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article proves the principles of developing the management system of an institution in the context of forming a positive image. It is clear that a positive image of an educational institution is the result of effective management, which covers organisational, pedagogical, financial and communication aspects, etc. The components of the image of an educational institution are presented. The image of an educational institution is dynamic and changes over time. It is shown that the management system plays a key role in creating and maintaining the reputation of the institution, which affects the trust of society, applicants, parents, employers, and other stakeholders. An educational institution's management system is an organisational structure that ensures effective management of the entire educational process. It includes a set of tools, methods, principles and instruments used to achieve the strategic goals of an educational institution. This system is aimed at optimising all aspects of the institution's functioning, such as the organisation of the educational process, management of the academic staff, infrastructure development, interaction with stakeholders, and the formation of the institution's image.It is vital to compete for applicants, resources and partnership opportunities, so the formation of a positive image is a top priority for the development of an educational institution. Education is not only a means of transferring knowledge, but also an important socio-economic tool that determines the competitiveness of an individual in the labour market. Successful development of the management system is impossible without the development of pedagogical culture and introduction of innovative teaching methods; the teaching staff, which actively develops and integrates new approaches, has a positive impact on the image of the institution and the results of the educational process.A well-formed image is a tool for communicating with the target audience. It creates a positive perception of the brand, helps to stand out among competitors and overcomes barriers such as distrust and indifference.
Keywords: image; image management; development; educational institution; competitiveness; management; innovation; efficiency